2016
DOI: 10.3897/bdj.4.e8692
|View full text |Cite
|
Sign up to set email alerts
|

CIGESMED for divers: Establishing a citizen science initiative for the mapping and monitoring of coralligenous assemblages in the Mediterranean Sea

Abstract: BackgroundOver the last decade, inventorying and monitoring of marine biodiversity has significantly benefited from the active engagement of volunteers. Although several Citizen Science projects concern tropical reef ecosystems worldwide, none of the existing initiatives has yet specifically focused on their Mediterranean equivalents. Mediterranean coralline reefs, known as “coralligenous”, are bioherms primarily built by calcifying rhodophytes on hard substrates under dim-light conditions; they are considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This process can be achieved in a more industrial, faster, and cheaper way rather than the classification of the individuals into species by professional taxonomists. Hence, cost-effective conservation initiatives may be designed and implemented while citizen science networks may also contribute towards this end through data gathering and reporting to scientists and managers (Gatti et al, 2016;Gerovasileiou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This process can be achieved in a more industrial, faster, and cheaper way rather than the classification of the individuals into species by professional taxonomists. Hence, cost-effective conservation initiatives may be designed and implemented while citizen science networks may also contribute towards this end through data gathering and reporting to scientists and managers (Gatti et al, 2016;Gerovasileiou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that advanced and professional divers are likely to be a strong pro-MCS group, and there are a number of possible interpretations of this finding. One reason could be that some scuba diving MCS projects require above-average scuba diving skills in order to carry out specific data collection tasks [ 3 , 65 ]. Experienced and professional scuba divers tend to also possess high levels of local ecological knowledge and other knowledge pertaining to the scuba diving sport (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sponges have been recently used as indicators of habitat quality in a small number of citizen science initiatives, e.g. in tropical coral reefs [ 37 ] and Mediterranean coralligenous formations [ 77 ]. The results of the present study confirmed the significant functional role of sponges, as a keystone taxon [see 2 ], for the marine cave habitat since the sponge functional pattern was highly correlated with the one derived from the analysis of the total community function, further highlighting the potential use of this taxon as an indicator for the monitoring of this particular habitat.…”
Section: Discussionmentioning
confidence: 99%